2018
DOI: 10.1021/acs.orglett.8b00991
|View full text |Cite
|
Sign up to set email alerts
|

Minisci-Photoredox-Mediated α-Heteroarylation of N-Protected Secondary Amines: Remarkable Selectivity of Azetidines

Abstract: The development of a general, mild, and functional-group-tolerant direct functionalization of N-heteroarenes by C–H functionalization with N-protected amines, including azetidines under Minisci-mediated photoredox conditions, is reported. A broad scope of substituted azetidines, including spirocyclic derivatives, and heterocycles were explored. This reaction enables the production of sp3-rich complex druglike structures in one step from unactivated feedstock amines and heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 33 publications
0
26
0
4
Order By: Relevance
“…[90] Almost simultaneously,B erthelot and co-workers published as imilar protocol that uses persulfate anion (Scheme 27). [91] An otable aspect of this transformation is its high chemoselectivity for HATadjacent to carbamate-protected amines, even in the presence of ethers.I nt he presence of either an alcohol group or at rifluoroacetylamine substituent, aB ocprotected a-amino radical is selectively heteroarylated. Both primary and secondary radical fragments can successfully undergo addition to arange of 6-membered heteroarenes.In ad irect competition experiment, N-Boc azetidine outcompetes oxetane for heteroarylation.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[90] Almost simultaneously,B erthelot and co-workers published as imilar protocol that uses persulfate anion (Scheme 27). [91] An otable aspect of this transformation is its high chemoselectivity for HATadjacent to carbamate-protected amines, even in the presence of ethers.I nt he presence of either an alcohol group or at rifluoroacetylamine substituent, aB ocprotected a-amino radical is selectively heteroarylated. Both primary and secondary radical fragments can successfully undergo addition to arange of 6-membered heteroarenes.In ad irect competition experiment, N-Boc azetidine outcompetes oxetane for heteroarylation.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In 2018, Wang and co‐workers showed that tert ‐butyl peracetate is an effective reagent for C−H abstraction from protected secondary amines, as well as other hydrogen atom donors, for a photoredox‐catalyzed Minisci‐type reaction . Almost simultaneously, Berthelot and co‐workers published a similar protocol that uses persulfate anion (Scheme ) . A notable aspect of this transformation is its high chemoselectivity for HAT adjacent to carbamate‐protected amines, even in the presence of ethers.…”
Section: Advances In Radical Generation Via Hydrogen Atom Abstractionmentioning
confidence: 99%
“…In another study, 1,5-naphthyridines 185 have been directly C-H functionalized in a single step with a variety of tert -butoxycarbonyl (Boc)-protected aliphatic and cyclic amines 184 under Minisci photoredox conditions from unactivated coupling partners ( Scheme 77 ). The high functional group tolerance and versatility of these transformations make them directly applicable to elaborate compounds 186 at the very last stage of synthesis [ 100 ].…”
Section: Reactivity Of 15-naphthyridinesmentioning
confidence: 99%
“…[87] 2018 zeigten Zhu und Mitarbeiter,d ass ähnliche Reagenzien auch Alkohole zu Alkoxyradikalen aktivieren kçnnen, welche durch HATw iederum weiter entfernte aliphatische C-H-Bindungen aktivieren, die im Anschluss Heteroarene alkylieren kçnnen. [91] Ein bemerkenswerter Aspekt dieser Umsetzung ist die hohe Chemoselektivität des HAT-Schrittes,d er selbst in Gegenwart von Ethern an Positionen in direkter Nachbarschaft zu carbamatgeschützten Aminen stattfindet. [89] Zhu und Mitarbeiter erkannten, dass dieser Ansatz auch füri ntermolekulare Minisci-Reaktionen nutzbar ist, in denen das radikalische Nukleophil an einer entfernten Alkylposition gebildet wird (Schema 26 b).…”
Section: Angewandte Chemieunclassified
“…[90] Nahezu zeitgleich verçffentlichten Berthelot und Mitarbeiter ein ähliches Syntheseprotokoll, in dem sie Persulfatanionen einsetzten (Schema 27). [91] Ein bemerkenswerter Aspekt dieser Umsetzung ist die hohe Chemoselektivität des HAT-Schrittes,d er selbst in Gegenwart von Ethern an Positionen in direkter Nachbarschaft zu carbamatgeschützten Aminen stattfindet. In Gegenwart einer Alkoholgruppe oder eines Tr ifluoracetylamin-Substituentenw ird ein Boc-geschütztes a-Aminoradikal selektiv heteroaryliert.…”
Section: Angewandte Chemieunclassified